Water use in China's power sector : impact of renewables and cooling technologies to 2030 (International Renewable Energy Agency ; China Water Risk, 2016)
This brief by China Water Risk and IRENA examines the expected impact of China's power sector on water and climate in 2030. Building on plans announced at the COP21 climate change conference in Paris, and earlier analyses by China Water Risk and IRENA, it assesses the impact of different options for China's power mix in 2030 on water use and carbon emissions. As the findings show, decarbonising the power sector through renewables would also yield benefits in areas related to water. By 2030, the combination of renewables and improved plant cooling technologies can reduce water-intensity in Chinese power generation by as much as 42%, while reducing emissions-intensity by up to 37%. To realise these benefits, the share of renewables must increase in line with national climate mitigation objectives and the REmap options outlined by IRENA.